Epitaxial Silicon Carbide Films Grown by New Method of Replacement of Atoms on the Surface of High-resistivity (111) Oriented Silicon - Bakranova Dina I.; Kukushkin Sergey A.; Nussupov Kair Kh.; Osipov Andrey V.; Beisenkhanov Nurzhan B. (MATEC Web of Conferences, 2016)
The nanolayers of single crystal SiC were grown on the surface of a high-resistance n-type silicon substrates by replacement of the atoms in the crystal lattice of silicon on the carbon atoms at the temperatures of 1250, 1330 °C and CO gas pressures 264, 395 Pa, respectively. The formation of crystalline β-SiC phase in films by electron diffraction and Raman spectroscopy techniques was shown. The SiC films are epitaxial and do not contain twins on the surface. By Atomic Force Microscopy is shown that two set of SiC films have pyramidal and step-like structure of the surface with clear-cut fragmentation of grains with sizes between 100 and 200 nm, and this is due to the composition of carbon and silicon atoms in the layer. Two set of SiC films have a granular surface structure with indistinct grain fragmentation. The influence of synthesis condition on the microstructure of film surface is discussed.